The Influence of Education, TNI-Polri Retirees and Independent Commissioners and Human Resources Development on Profitability - Novarialdi Novarialdi (Jurnal Akuntansi Trisakti, 2022)
Abstract     This study aims to examine the effect of the educational background of the director of operations and the board of commissioners, the presence of retired TNI-Polri as commissioners, the proportion of independent commissioners and the cost of developing human resource competencies on on the financial performance of SOEs. Financial performance is proxied by Return on Assets (RoA), educational background is proxied by education according to the company's line of business, retired TNI-Polri as commissioners are proxied by the presence or absence of commissioners who are retired TNI-Polri . Independent commissioners are proxied by the number of independent commissioners to the number of commissioners, while competency development is projected by the realization of costs for development and training.The research sample consisted of 15 State-Owned Enterprises listed on the Indonesia Stock Exchange (IDX) during the period 2016 to 2019, so that 60 samples were obtained. The analytical method used to test the hypothesis in this study is the multiple regression analysis method of panel data. The results of this study indicate that the educational background variable has a negative effect on profitability, commissioners who come from retired TNI-Polri have no effect on profitability, the proportion of independent commissioners has a positive effect on profitability and the cost of developing human resource competencies has a positive effect on profitability.